Molecular analysis of immunoglobulin variable genes in human immunodeficiency virus-related non-Hodgkin’s lymphoma reveals implications for disease pathogenesis and histogenesis - Daniela Capello; Maurizio Martini; Annunziata Gloghini; Michaela Cerri; Silvia Rasi; Clara Deambrogi; Davide Rossi; Michele Spina; Umberto Tirelli; Luigi Maria Larocca; Antonino Carbone; Gianluca Gaidano (Haematologica, 2008)
Background Human immunodeficiency virus (HIV)-related non-Hodgkin’s lymphomas (HIV-NHL) are heterogeneous and associated with distinct molecular pathways. Analysis of immunoglobulin variable genes (IGV) may provide insights into the pathogenesis and histogenesis of HIV-NHL.Design and Methods IGV rearrangements were amplified from genomic DNA by polymerase chain reaction and directly sequenced in 87 cases of HIV-NHL (17 Burkitt/Burkitt-like lymphomas, 38 diffuse large B-cell lymphomas, and 32 primary central nervous system lymphomas).Results A skewed IGHV repertoire in specific HIV-NHL clinico-pathological categories was observed. Systemic HIV-diffuse large B-cell lymphomas displayed underrepresentation of the IGHV3 family (11/38, 28.9%; p=0.0047) and, in particular, of the IGHV3–23 gene (0/38; p